Classification of oil palm nitrogen status from SPOT-6 satellite using support vector machine and spectral indices - Amirruddin, Amiratul Diyana; Muharam, Farrah Melissa (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Nitrogen (N) management is important in sustaining oil palm production. Remote sensing based approaches such as spectral index has promise in assessing the N nutrition content of many crops. The objectives of this study are to examine the N classification capability of three spectral indexes (SI): visible (Vis), near infrared (NIR) and a combination of visible and NIR (Vis+NIR) using data from the SPOT-6 satellite. N treatments varied from 0 to 2 kg per palm and were applied to both mature palms. The N-sensitive SIs tested in this study were age-dependent. The Vis index such as BGRI1 (CVA= 79.55%) and the Vis+NIR indices such as NDVI, NG, IPVI and GNDVI (CVA= 81.82%) were the best indices to assess N status of young and prime mature palms through the SVM classifier. Nonetheless, the SVM classifier showed promising potential in classifying foliar N content of mature palms that can possibly be used further for developing a new index in assessing N content of oil palms.